Optical and gamma-ray study of gamma-ray binaries - Monageng, Itumeleng (Department of Astronomy, 2019)
Gamma-ray binary stars are intriguing interacting stellar systems that exhibit emission across the whole electromagnetic spectrum. This thesis is focused on optical and gamma-ray emission of gamma-ray binary stars (GRBis). I have performed radial velocity measurements of 1FGL J1018.6-5856 to derive the orbital parameters of the system. In particular, I derive, for the first time, the orbital eccentricity which, together with other parameters, enables us to attain the orbital geometry of the system. I also use the derived parameters to put constraints on the mass of the compact object. For a large range of orbital inclination angles, a neutron star is favoured, while a black hole is allowed for very low inclination angles. I have also explored the long term variability of the Be disc in LS I +61 303. Using the measured parameters of the Hα emission line together with a semi-analytical model which describes the motions of particles in the disc, I examine long term geometric changes of the Be disc in LS I +61 303. I have explored different possible scenarios for the Be disc changes by studying the variability of the eccentricity and argument of pericenter on the superorbital timescale. One of the effects we have examined from the implication of our results is the Kozai Lidov mechanism, which has so far only been explored theoretically. I have explored the Bethe-Heitler mechanism for the production of gamma-ray emission, where energetic protons collide with stellar photons to produce energetic electron-positron pairs which upscatter photons to high energies. This mechanism has been neglected in studies of photo-hadronic processes due to the larger radiative efficiency of pion production. I demonstrate, however, that the BetheHeitler process can dominate the radiative output at lower proton energies where pairs can form but not pions. I calculate the spectrum and modulated flux in the context of the pulsar wind scenario, with photon-photon absorption and cascading effects taken into account. The effects of the ambient magnetic field around the massive star are also considered, which result in quasi-isotropic gamma-ray emission, and the orbital modulation of the flux resulting in photon-photon absorption. The work presented in this thesis encompasses different observational and theoretical aspects of gamma-ray binaries in which I use data and modeling to address some of the puzzling features of these systems. These include understanding the nature of the compact object, and thereby the physical mechanism driving the multiwavelength emission, the variability of the Be disc and its long term interaction with the compact object, and the origin of high energy emission. The results and methods presented have potential implications not only for understanding these objects, but also for other classes of interacting binaries.